2009
DOI: 10.1007/s00595-009-3945-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary perivascular epithelioid cell tumor (PEComa) of the liver: Report of a case

Abstract: PEComa is very rare mesenchymal neoplasm which is formed by perivascular epithelioid cells and is characterized by dual melanocytic and myoid differentiation. Up to now only a very few cases of PEComa of the liver have been described worldwide. We herein present a patient who underwent a right hemihepatectomy for a huge tumor which could not be identified by imaging investigations. A final histopathologic examination revealed a benign epithelioid tumor with a solid growth pattern, abundant vascularity, and fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 20 publications
3
23
1
1
Order By: Relevance
“…In agreement with others [3,16] the tumor cells in our case were S-100 negative. Contrary to us and to most reports, some authors reported patchy S-100 staining of PEComa cells [6,11]. In the present study the immunoexpression of CD-10 was negative in the tumor cells, although in some cases of PEComas positivity for CD-10 was noted.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In agreement with others [3,16] the tumor cells in our case were S-100 negative. Contrary to us and to most reports, some authors reported patchy S-100 staining of PEComa cells [6,11]. In the present study the immunoexpression of CD-10 was negative in the tumor cells, although in some cases of PEComas positivity for CD-10 was noted.…”
Section: Discussioncontrasting
confidence: 99%
“…To date, the extremely rare perivascular epithelioid cell tumor has been described in various anatomic locations: in lungs [1], pancreas [2], uterus [6,7], bone [8], retroperitoneum [9], ovary [10], liver [11], cutis [12], transverse colon [4] and in intraorbital location [3]. As was mentioned above, close perirenal location concerns only three cases of PEComas [5,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor sizes ranged between 1.5 and 20 cm. Four patients had normal levels of serum AFP and were negative for hepatitis B surface antigen and anti-hepatitis C virus antigen (6,10,12,15); reports of the other 8 cases did not mention this. Two patients had a history of melanoma (13,14), and 1 had a history of GIST (8).…”
Section: Discussionmentioning
confidence: 87%
“…Generally, indigestion, loss of appetite, nausea, body weight loss, and intermittent colic pain can occur, and on physical examination tenderness to palpation and liver enlargement may be observed. These tumors have occurred in female patients aged from 13 to 70 years (median age: 55) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Of the reported 12 cases (5-15), 6 cases occurred in the left lobe (7-9, 11, 14, 15), 4 in the right lobe (5,6,10,12), 1 in the caudate lobe (7), and 1 in the ligamentum teres (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation